Diseño de juego interactivo para niños, sin programación y con ayuda de inteligencia artificial - Morales Mence, Ariana Daniela; Ladines Molina, Geovanna Vanessa; Ortega Vaca, Nathaly Briggitte (Scripta Mundi, 2023)
The objective of this project is to design an interactive game with the help of Artificial Intelligence programs applied in graphic design, to teach children about caring for the environment without the need for programming, using Adobe InDesign. A bibliographic research is carried out to understand the key concepts and best practices in environmental education and educational game design. A descriptive-qualitative research is carried out that includes the opinion of a psychologist to review the game. The game design includes a level with three sub-games, addressing topics such as recycling, saving and reusing. Scenarios are created that encourage participation and meaningful learning. In the conclusions and recommendations, the ease of designing educational games without programming with Adobe InDesign is analyzed in the context of environmental pedagogy and recommendations are provided for educators and designers interested in using this methodology, identifying possible areas of improvement or future research.